The Development of L2 Oral Language Skills in Two L1 Groups: A 7‐Year Study. Issue 2 (7th March 2013) - Derwing, Tracey M.; Munro, Murray J.
Abstract : Researching the longitudinal development of second language (L2) learners is essential to understanding influences on their success. This 7‐year study of oral skills in adult immigrant learners of English as a second language evaluated comprehensibility, fluency, and accentedness in first‐language (L1) Mandarin and Slavic language speakers. The primary data were judgments at three times from two sets of listeners: native monolingual speakers of English and highly proficient English L2 speakers. The Mandarin L1 speakers showed no change over time on any of the dimensions, while the Slavic language L1 speakers improved significantly in comprehensibility and fluency. Improvement in accent was limited to the first 2 years in the Slavic language group. These outcomes appear to be due to the complex interplay of L1, age, the depth and breadth of learners' conversations in English, and their willingness to communicate.